Hubungan Self Managementt terhadap Kepatuhan Konsumsi Obat Hipertensi pada Lansia di Desa Cot Cut Kecamatan Kuta Baro Aceh Besar (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The high number of hypertension cases is due to the still low level of hypertension control, specifically medication adherence. Treatment adherence is crucial for maintaining health and well-being in patients with hypertension. In contrast, non-adherence to medication leads to treatment failure. This study aims to determine the relationship between self-management and adherence to hypertension medication in the elderly. This research employed an analytical design with a cross-sectional approach. The study consisted of 49 elderly people with hypertension in Cot Cut Village, Kuta Baro, Aceh Besar. The sample was chosen using a total sampling technique. The MMAS-8 questionnaire was used to assess adherence to hypertension medication with a Cronbach's alpha of 0.860. The self-management questionnaire showed a Cronbach's alpha of 0.766. The research was conducted from April 8th to 14th, 2025. The data analysis used univariate and bivariate methods, using the chi-square test. The results showed that out of 49 respondents, 21 (42.9%) were less adherent to hypertension medication, and 29 (59.2%) had less adherence to self-management. The chi-square test indicated a p-value of 0.001, showing a relationship between self-management and adherence to hypertension medication among the elderly. This research suggests that hypertensive patients should be supervised to improve medication adherence and self-care management to maintain stable blood pressure.